Significance of the shareholder rights’ application in the Turkish banking sector under the corporate governance principles - Acarlı, Adem (My University, 2008)
KURUMSAL YÖNETİM İLKELERİ ALTINDA TÜRK BANKACILIK SEKTÖRÜNDE HİSSEDAR HAKLARININ UYGULANMASININ ÖNEMİ Küreselleşmenin dünyada daha yaygın olduğundan beri günümüzde kurumsal yönetim uygulamaları dünya ekonomisinde faaliyet gösteren tüm firmalar için ana başarı faktörlerinden biri olmuştur. Hissedar haklarının korunması kurumsal yönetim ilkelerini uygulanmasının önemli bir parçasıdır. Özellikle de azınlık hissedar haklarının korunması Türkiye gibi kıta avrupası hukukuna dahil ülkelerde geliştirilmesi gereken bir konudur. Bu noktada bankaların, özelliklede hisse senetleri borsada işlem gören bankaların, hissedar haklarına daha fazla önem vermeleri gerekmektedir. Bankalar ekonomide diğer kurumlardan daha fazla sosyal paydaşa sahiptirler. Bu nedenle bu sektördeki kötü kurumsal yönetim, geçen kasım 2000 ve şubat 2001 finansal ve bankacılık krizlerinde olduğu gibi, ekonominin tüm taraflarını özelliklede hissedarlar ve sosyal paydaşları diğer sektörlerden daha fazla etkilemektedir. Bu tezde Türk bankacılık sektörü, sektördeki hissedar hakları kurumsal yönetim ilkeleri altında incelenmeştir. Sektöredeki banklar ve bu bankaların hissedarlarının hakları, bu hakların önemi ve bankalarla, şirketlere getireceği faydalara yer verilmiştir. Bankaların yeni düzenlemeler doğrultusunda neler yapması gerektiği, mevcut durumları açıklanmaya çalışılmıştır. Ayrıca sektörde hissedar ve azınlık hissedarlar açısından geliştirilmesi gereken alanlarda önerilerde bulunulmuştur.

SIGNIFICANCE OF THE SHAREHOLDER RIGHTS’ APPLICATION IN THE TURKISH BANKING SECTOR UNDER THE CORPORATE GOVERNANCE PRINCIPLES Nowadays corporate governance applications are key success factor for every company that perform in the world economy since the globalization has became more spread throughout the world. Protection of the shareholders rights is the most important part of the application of the corporate governance principles. Especially protection of the minority shareholders should be improved in the civil law countries, the countries such as Turkey. At this point banks should give more consideration to the shareholder rights especially the banks have their stocks perform in the stock market. The banks are the associations that have more stakeholders than the other companies in the economy. So that every issue occurred in this sector due to the bad corporate governance, affects to all parts of the economy more than other sectors, especially the shareholders and the stakeholders as it happened during the last financial and banking crises on November 2000 and February 2001 in Turkey. In this thesis Turkish banking sector and the shareholder rights in this sector under the corporate governance principles are investigated. The relationship between the banks and the shareholder rights in this sector, importance of these rights and benefits to the banks and companies are reviewed. The necessities related with the improvement of the banks through new regulations and banks’ current situations are stated. Finally some policy recommendations are suggested for the development of the banking sector in terms of shareholder and the minority shareholder rights
Keywords: Azınlık Hissedar Hakları; Bankalar ve Bankacılık_Türkiye; Hissedar Hakları; Kurumsal Yönetim; Muhasebe